Validity and reliability of the Hexoskin wearable biometric vest during maximal aerobic power testing in elite cyclists - Elliot, C. A.; Hamlin, M. J.; Lizamore, C. A. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to investigate the validity and reliability of the Hexoskin vest for measuring respiration and heart rate (HR) in elite cyclists during a progressive test to exhaustion. Ten male elite cyclists (age 18-52 yrs, height 179.3 ± 6.0 cm, body mass 73.2 ± 9.1 kg, 2max">VO2max 60.7 ± 7.8 ml·kg·min-1, mean ± SD) conducted a maximal aerobic cycle ergometer test using a ramped protocol (starting at 100 W with 25 W increments each min to failure) during 2 separate occasions over a 3-4-day period. Compared with the criterion measure (MetaMax 3B) the Hexoskin vest showed mainly small typical errors (1.3-6.2%) for HR and breathing frequency (f), but larger typical errors (9.5-19.6%) for minute ventilation (VE) during the progressive test to exhaustion. The typical error indicating the reliability of the Hexoskin vest at moderate-intensity exercise between tests was small for HR (2.6-2.9%) and f (2.5-3.2%) but slightly larger for VE (5.3-7.9%). We conclude that the Hexoskin vest is sufficiently valid and reliable for measurements of HR and f in elite athletes during high-intensity cycling but the calculated VE value by the Hexoskin vest produced during such exercise should be used with caution because of the lower validity and reliability of this variable.